Software Solution for Social Media Data Compilation and Analysis - Krajnc, Elmar (2014)
This project was developed in the winter semester of 2013, as an initiative of the Research and Development Group, KMU goes Mobile, from the IT Department of the FH Joanneum, University of Applied Sciences, in Kapfenberg, Austria. Two main parts compose the project itself. First the research on Social Media Marketing for Small and Medium Enterprises and second: the development of a Web Based Adaptable Software Solution for Social Media Data Compilation and Analysis, both of them to be detailed in the current document.